Processing Effects on the Formability of Extruded Flat Products of Magnesium Alloys - Nienaber, Maria; Kainer, Karl Ulrich; Letzig, Dietmar; Bohlen, Jan (Frontiers in Materials, 2019)
The development of microstructure and texture during flat product extrusion of magnesium alloys differs significantly from those of rolled sheets. It has especially been shown that the range of microstructures and textures is broad in the case of extrusion which allows significant variations of the resulting textures. Three wrought magnesium-zinc alloys with texture modifying elements Nd (ZN10), Ca (ZX10) and Al (AZ31) have been used to extrude flat band profiles with varied processing parameters. This allowed a distinct variation of grain sizes and textures of the extrudates. The impact on the mechanical properties and the forming behaviour (Erichsen values IE) is revealed and discussed with respect to the microstructure and texture. It can be shown that a weak alignment of basal planes is preferred for enhanced formability over a distinct alignment of basal planes even if oriented preferentially for basal slip.